Association Between Sociodemographic, Child Behaviour and Parent's Child Feeding Practice With Nutritional Status among Standard One School Children in Kota Kinabalu - Nachia Banu Abdul Rahim; Fredie Robinson; Zulkhairul Naim Sidek Ahmad; Nabihah Ali; Mohd Hafizuddin Ahmad (Universiti Putra Malaysia, 2023)
Introduction: Childhood malnutrition, caused by multiple factors and linked to various health issues, is a significant public health concern. Therefore, this study aimed to estimate the prevalence of malnutrition among primary school children in Kota Kinabalu and its associated factors. Methods: This cross-sectional study was conducted among Standard One primary school children (7 years old). The BMI-for-age was calculated, the Child Physical Activity Questionnaire (CPAQ) and the Child Feeding Questionnaire (CFQ) were utilised to assess the contributing factors. While multinomial regression is used to predict the probability of different outcomes. Results: In this study, 35.5% of children were underweight and 13.2% were overweight. Boys (OR 0.7; 95% CI 0.522-0.931) and children without a TV in view during meals (OR 0.740; 95% CI 0.549-0.997) were less likely to be underweight. Children of Kadazan ethnicity (OR 1.964; 95% CI 1.055-3.658) were more likely to be overweight than others. Parents of overweight children felt less responsible for their child’s feeding (OR 0.67; 95% CI 0.521-0.863) and perceived their child (OR 3.245; 95% CI 1.745-6.034) and themselves as heavier (OR 1.822; 95% CI 1.023-3.244). In contrast, parents of underweight children perceived their children to be lighter (OR 0.425; 95% CI 0.284-0.637). Finally, parents of overweight children put less pressure on their children to eat (OR 0.584; 95% CI 0.448-0.761) than parents of normal and underweight children. Conclusion: Addressing the complex interplay between socio-cultural factors and parental attitudes in childhood malnutrition is crucial in designing effective interventions to combat malnutrition and promote healthier lifestyles.